1974
DOI: 10.3171/jns.1974.41.2.0217
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological effects of dorsal column stimulation in man and monkey

Abstract: ✓ In 18 patients with cancer and intractable pain, capacitatively coupled pulses of 0.25 msec duration were delivered transcutaneously at 100 Hz to sets of five in-line electrodes implanted subdurally over the dorsal columns. Averaged somatosensory-evoked potentials were recorded from scalp electrodes before, during, and after application of current. All but one patient experienced relief of pain during stimulation, persisting for as long as several hours afterward. Eleven patients developed hyperactive deep r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

1975
1975
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 8 publications
2
49
0
2
Order By: Relevance
“…Thus, somatosensory-evoked potentials re corded from the scalp of patients have been found to be reduced in ampli tude during and, in some cases, even following cessation of DCS. Larson et al [6], N yquist and G reenhoot [9], as well as Bantu et al [2] ob tained a reduction in evoked potential amplitude in the cortex, in thalam ic nuclei and in the spinal cord in association with DCS. Lastly, at the cel lular level, D ong and Wagman [4] have reported a reduction in firing of cells in the thalamic posterior group of nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, somatosensory-evoked potentials re corded from the scalp of patients have been found to be reduced in ampli tude during and, in some cases, even following cessation of DCS. Larson et al [6], N yquist and G reenhoot [9], as well as Bantu et al [2] ob tained a reduction in evoked potential amplitude in the cortex, in thalam ic nuclei and in the spinal cord in association with DCS. Lastly, at the cel lular level, D ong and Wagman [4] have reported a reduction in firing of cells in the thalamic posterior group of nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The pain re lief produced by DCS, however, could be due to mechanisms other than interactions in the dorsal horn. Thus, it has been shown in Rhesus mon keys that pathways in the ventral as well as in the dorsal quadrants of the cord are activated by DCS [2], and there is evidence in humans [5,6] as well as in animals [3,9] that DCS affects neuronal responsiveness in su-praspinal areas. The present communication extends these concepts by reporting the effect of DCS on single neuronal activity of the thalamus in one patient who underwent stereotaxic thalamotomy following previous implantation of a dorsal column stimulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockage of pain at the spinal dorsal horn and the spinothalamic tract occurs by retrograde impulse conduction, which activates inhibitory neurons, increases GABA release, and reduces excitatory glutamic acid level. Other mechanisms have also been reported: activation of the descending pain suppression pathway and direct stimulation of the thalamus by SCS ascending impulses, leading to pain relief and improvement of failed sensory modulation action in the basal ganglia [4,[13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the analgesic action of spinal cord stimulation (SCS) was based initially on the gate control theory of pain proposed by Melzack and Wall [3]. On the other hand, it has been suggested that the SCS has multiple analgesic actions by acting on any abnormal activity in the A-β neurons that receive pain, restoring the normal gamma amino butyric acid levels in the dorsal horn, and releasing adenosine in the central nervous system [4,5]. In the spinal cord, pain modulating neurotransmitters, such as substance-P, and sero tonin, are released by SCS [6].…”
Section: Introductionmentioning
confidence: 99%